The process of becoming black in Noviolet Bulawayo's We Need New Names - Ayaicha, Somia; Mani, Manimangai; Kaur, Hardev; Awang, Mohamed Ewan (Librairie du Liban Publishers, 2021)
The bruised voices of African immigrants in America have been portrayed in contemporary African literature, such as NoViolet Bulawayo’s We Need New Names (2013). According to Bulawayo’s depiction, Darling is among those who are subjected to racial discrimination which was never an issue for them back in their countries. This article attempts to bridge the literary field with social psychological theories by examining the influence of African immigrants’ social identifications and categorizations, using Tajfel and Tuner’s Social Identity Theory. Moreover, the concept of individual mobility is explored as a coping mechanism by the immigrants to deal with their negative social identity. The second objective is the identification of the various phases that African immigrants go through during the process of becoming black. This can be achieved through the use of William Cross’ Nigrescence Theory. A significant contribution of the present paper lies in analyzing African immigrants from a different perspective, focusing more on the journey of self-acceptance and the process of becoming black through the Nigrescence theory. The inclusion of these theories, namely Social Identity and the Nigrescence theory, is a broadening input in literary analysis since they have not been applied in previous literary studies.